32 Quantifying the Prevalence of Frailty in Drug Trials and the Relationship with Serious Adverse Events. (16th March 2021) - Hanlon, P; Butterly, E; Lewsey, J; Siebert, S; Mair, F S; McAllister, D A
Abstract: Introduction: Frailty is common in clinical practice, but trials rarely report on participant frailty. Consequently, clinicians and guideline-developers assume frailty is largely absent from trials and have questioned the relevance of trial findings to frail people. Therefore, we examined frailty in phase 3/4 industry-sponsored clinical trials of pharmacological interventions for three exemplar conditions: type 2 diabetes mellitus (T2DM), rheumatoid arthritis (RA), and chronic obstructive pulmonary disease (COPD). Methods: We constructed a 40-item frailty index (FI) in 19 clinical trials (7 T2DM, 8 RA, 4 COPD, mean age 42–65 years) using individual-level participant data. Participants with a FI >0.24 were considered "frail". Baseline disease severity was assessed using HbA1c for T2DM, Disease Activity Score-28 (DAS28) for RA, and % predicted FEV1 for COPD. Using generalised gamma regression, we modelled FI on age, sex and disease severity. In negative binomial regression we modelled serious adverse event rates on FI, and combined results for each index condition in a random-effects meta-analysis. Results: All trials included frail participants: prevalence 7–21% in T2DM trials, 33–73% in RA trials, and 15–22% in COPD trials. Increased disease severity and female sex were associated with higher FI in all trials. Frailty was associated with age in T2DM and RA trials, but not in COPD. Across all trials, and after adjusting for age, sex, and disease severity, higher FI predicted increased risk of serious adverse events; the pooled incidence rate ratios (per 0.1-point increase in FI scale) were 1.46 (95% CI 1.21–1.75), 1.45 (1.13–1.87) and 1.99 (1.43–2.76) for T2DM, RA and COPD, respectively. Conclusion: Frailty is identifiable and prevalent among middle aged and older participants in phase 3/4 drug trials and has clinically important safety implications. Trial data may be harnessed to better understand chronic disease management in people living with frailty.